To the respectable publick : Certain resolves having been proposed by the Committee of Correspondence, to a number of citizens assembled at the coffee-house yesterday, and rejected ... they proceeded to nominate a new committee for the purpose, and appointed us the subscribers on it . - Low, Isaac, 1735-1791 (LLMC-digital (Series), 1774)
Declining the appointment to the committee of delegates to the Continental Congress offered by the Committee of Correspondence.